ANALISIS YURIDIS SISTEM PEMBIMBINGAN KLIEN PEMASYARAKATAN DI BALAI PEMASYARAKATAN (BAPAS) KLAS I MALANG - Enny Umronah (Legal Spirit, 2019)
Mentoring is a series of law enforcement through the unity of life relationship efforts, life and the livelihood of the inmates in a social life. so they can realize their mistake, improve theirselves and not to repeat the criminal act and be accepted by the environment, by improving the inmates quality, devotion to God the Almighty, intellectual, attitude and behavior, professional, physical and spiritual health of However, the mentoring process was not carried out optimally, resulting the offense of law happen again that is why the thesis titled judicial analysis of the mentoring of penitentiary client system in Balai Pemasyarakatan Kelas I Malang. This study was intended to describe how does the inmate mentoring penintetiary system in Balai Pemasyarakatan Kelas I Malang ?, what factors that affect the implementation of the inmate in Balai Pemasyarakatan Kelas I Malang ?. Furthermore, this study aims to describe and explain the inmates mentoring system also elaborates and analyzes the factors that influence the mentoring system of the inmate in Balai Pemasyarakatan (BAPAS).Keywords: Guidance, Penitentiary, Penitentiary (Bapas)